The recognition of children's voices in health care and research within Nigerian child protection legislation: A normative analysis - Shilni J. Liberty; Franco A. Carnevale (Elsevier, 2021)
There is a growing body of knowledge about children as moral agents and their capacity and interest to participate in healthcare and research discussions/decisions that affect them. Although this has led to some research and practice improvements that have better-recognized children's voices, this trend has not been globally embraced, especially within Sub-Saharan Africa. Objective: This study examines and analyzes the rights of children to participate in healthcare and research discussions and decisions within the normative discourse of child protection laws in Nigeria. Method: We conducted a normative documentary analysis based on five of the principal Nigerian child protection legislative documents enacted from 1999 to 2019. Results: Findings demonstrated that Nigerian legislation acknowledges the participation rights of children in healthcare and research. However, the normative document also emphasized children's obligation to the given privileges in the form of respect to parents/guardians, superiors, and elders. Conclusion: Norms regulating the rights of children are in existence in Nigeria. Nevertheless, legal guidance to ethical practice in healthcare have been generalized and has not upheld the idea of dignity and liberty of children. We recommend that Nigeria should reconsider the code of ethical practices in the fields of health and research to give children the participatory authority that could provide active involvement and compliance.